Individualization practices in regular and special education preschool programs for children with autism - Primero, Maria Pamela Bautista (2005)
Assessment, curriculum, methods of teaching, instructional materials, teacher preparation for classroom teaching, classroom set-up, and parental involvement were investigated in this study. Results of the study revealed that regular preschool programs conduct individualized practices in assessment, curriculum, methods of teaching, instructional materials, teacher preparation for classroom teaching, classroom set-up, and parental involvement. The SPED preschool programs carry out highly individualized practices in assessment, curriculum, teacher preparation for classroom teaching, classroom set-up, and parental involvement, and individualized practices in methods of teaching and instructional materials.